Adult Saethre-Chotzen Syndrome: A Unique Abnormal Breathing Pattern. Issue 5 (July 2021) - den Ottelander, Bianca; Gaillard, Linda; Yang, Sumin; de Goederen, Robbin; Bredero-Boelhouwer, Hansje; van Veelen, Marie-Lise; Tasker, Robert; Joosten, Koen; Mathijssen, Irene
Abstract : Abstract: A 35-year-old male with Saethre-Chotzen syndrome presented with severe complaints. Neuroimaging showed a Chiari-I malformation, mild ventriculomegaly, a syrinx of the wide central canal, and various cerebral vascular anomalies including a large occipital emissary vein on the right. Ultrasound of this vein confirmed blocking of the outflow-track when turning his head to the right, which also provoked the headaches and bruit. Polysomnography revealed severe positional sleep apnea with a mixed breathing pattern, the central components consisted of periodic breathing with, at times, crescendo-decrescendo reminiscent of a Cheyne-Stokes versus Biot breathing pattern, pointing to possible brain stem/pontine problems. Continuous positive airway pressure was initiated, and the patient was instructed to avoid sleeping in the right lateral position. One year later, nearly all his complaints have resolved. A questionnaire was sent to all adult Saethre-Chotzen patients in our craniofacial unit, none reported any of the severe symptoms as described by our index case.